Aries Agro : leveraging iotin facility logistics - Roy, Debjit, (SAGE business cases., 2020)
This case identifies the key challenges faced by an agribusiness firm - improving worker safety and productivity. The firm is contemplating the implementation of an IoT-based solution to overcome these challenges. This IoT-based solution captures the movement of workmen and generates data that will be used to identify sources of inefficiency. From this data, we calculate the day-wise efficiency and productivity of operators. Based on the study, we infer that there was a lot of randomness and redundancy in the workmen's movements. These findings are then used to come up with a new layout for the shop floor.